Performance of bioclimatic design strategies at residential college buildings in University of Malaya / Adi Ainurzaman Bin Jamaludin - Jamaludin, Adi Ainurzaman (2014)

(untitled)
Preliminary studies of twelve residential colleges located in the University of Malaya campus, Kuala Lumpur were conducted to evaluate the effectiveness of their current implementation of bioclimatic design strategies, as well as their performance in terms of electricity usage. It was found that residential college buildings designed with an internal courtyard and balconies for each room achieve the most efficient electricity use, within a range of between 24 to 33 kWh/m2/year, while other residential college buildings recorded annual electricity use of between 40 to 125 kWh/m2/year. One of them, 5th residential college (5th RC) was selected for the case study due to its best implementation of bioclimatic design strategies that encourage efficient energy use. Furthermore, its uniform building layout minimises uncontrolled variables in further field investigation and evaluations. The satisfaction and perception surveys show that a majority of respondents at 5th RC are at a comfortable level. This is based on findings from all performance indicators of functional elements, thermal comfort and indoor air quality, as well as, visual comfort and landscape elements. The 5th RC is capable to provide a comfortable living space with indoor temperatures ranging from 28°C to 30°C with 70% to 78% relative humidity. Different locations have different effects on room conditions and higher temperatures were recorded at rooms on the top level of the building compared to rooms at the lower levels. There were no significant differences detected owing to different orientation of rooms which are largely due to the effects of the green landscape. Higher values of daylight intensity were recorded in the corridor compared to the daylight intensity in the rooms which even varies in amount at different areas within the same room. Further analysis show that night ventilation provides better thermal comfort for residents compared to other ventilation options like full-day and daytime ventilation or no ventilation at all. The living behaviour assessment reveals that residents of 5th RC have adapted well to maintain the comfort level in their rooms. Only light activities were conducted in the rooms which reduces the metabolic heat production. Ceiling fans were fully utilized at the maximum speed of five for maintaining air circulation in the rooms where the operable windows are closed most of the time due to the safety issues. Light clothing was worn at most times, especially on sunny days. In fulfilling the need for privacy, curtains have been overused and leading to the use of artificial lighting. The study concludes, residential college buildings that implement the appropriate bioclimatic design strategies, particularly to address natural ventilation and daylighting issues tend to achieve a desired comfort level and efficient electricity usage. With a well-planned design improvement, better results can be achieved without sacrificing the needs and comfort level of the residents.